Credit Cyclicality in Chile : A Cross-Country Analysis - Soderling, Ludvig (IMF Working Papers; Working Paper ;, 2008)
This paper analyzes the determinants of credit cyclicality. It constructs a financial development index and studies whether it affects the amplitude of impulse responses to shocks to output, terms of trade, global liquidity, and global risk appetite. The paper uses both country-specific VARs for cross-country analyses and panel VARs to compare impulse responses between various country groupings. The study finds evidence that financial development-especially stronger creditor rights-can mitigate credit cyclicality, given that the response of credit to output or terms of trade shocks is stronger in countries with weaker financial systems.